FOREWORD - Epure, Manuela (Journal of Economic Development, Environment and People, 2020)
What is needed to create a more sustainable world for us and for future generations? This is a question araised more often than ten years ago, just because of the concern about humankind's future is blurry, environmental issues become an urgency due to the visible consequences: floods, bushfires without precedent like recent Australian tragedy. The population and governments can no longer ignore these signs and immediate actions are required. The United Nations Sustainable Goals (SDGs) lay out how to eradicate poverty, advance environmental sustainability and provide decent housing, clean water and health care and education to those disadvantaged ones. All UN member states committed to take appropriate measures to make SDGs achievable as soon as possible. However, all beautiful ideals need finance to become a reality. UN estimates about $6 trillion a year to properly address all 17 SDGs, but this amount far exceeds the traditional sources that can be attracted. Therefore, global finance people think that the entire global capitalist system should get involved and contribute. At the core of this idea is the understanding that when businesses apply their expertise to solve problems, create profit and progress can go together for a better society, business and environment. Companies must consider their long-term financial sustainability in light of these global challenges and maintain a healthy environment and workforce. As an example, in SUA the Environmental Business Initiative, the funds to be deployed are $445 billion between 2007 to 2030 to support the transition to a low-carbon sustainable economy. The general public is asking businesses to take sustainability always into consideration in all their decisions. In one study, 81 percent of Millenials said companies must have a major role in driving SDGs[1]. Also, growing evidence shows a correlation between sustainability practices and better financial performance, higher productivity and lower risks[2]. It seems if businesses can deliver profitability, shareholder return than they could support the SDs most relevant to their businesses. Simple as that. [1] https://www.goldstandard.org/sites/default/files/documents/sdg_report_optimized.pdf [2] https://www.spglobal.com/en/research-insights/articles/the-esg-advantage-exploring-links-to-corporate-financial-performance